Sideritis romana L. subsp. purpurea (Tal. ex Benth.) Heywood, a new chemotype from Montenegro. Issue 9 (3rd May 2018) - Garzoli, Stefania; Božović, Mijat; Baldisserotto, Anna; Andreotti, Elisa; Pepi, Federico; Tadić, Vanja; Manfredini, Stefano; Ragno, Rino
Abstract: A study on essential oil fractions of the Western Balkan endemic Sideritis romana L. subsp . purpurea (Tal. ex Benth.) Heywood collected in Montenegro is reported. The 24-h systematic steam distillation extraction procedure was performed. The gas chromatographic/mass spectrometric (GC/MS) analysis of the fractions showed γ -elemene and spathulenol as two main constituents, revealing a new chemotype of this plant species. Although varying in the content of these two main compounds, which makes the fractions quite different between each other, evaluation of the anti- Candida activity showed the lack of any significant efficacy. Abstract :